Signals, systems & inference - Oppenheim, Alan V., 1937-; Verghese, George C. (Pearson, 2017)
For upper-level undergraduate courses in deterministic and stochastic signals and system engineering. An Integrative Approach to Signals, Systems and Inference. Signals, Systems and Inference is a comprehensive text that builds on introductory courses in time- and frequency-domain analysis of signals and systems, and in probability. Directed primarily to upper-level undergraduates and beginning graduate students in engineering and applied science branches, this new textbook pioneers a novel course of study. Instead of the usual leap from broad introductory subjects to highly specialized advanced subjects, this engaging and inclusive text creates a study track for a transitional course.